Transfer of effect of dry-land resistance training on speed and parameters of swimming technique - Sadowski, J. (Theory and Practice of Physical Culture, 2020)
The aim of the study was to determine the type and size of the cumulative transfer of the effect of dry-land upper limb resistance training on the speed and parameters of swimming technique. The study involved (n = 40) physical education students aged 21.3 ± 1.8 years, body weight: 79.1 ± 2.4 kg, body height: 179.8 ± 2.7 cm. The participants were randomly divided into three groups, i.e. two experimental groups: T (n = 16) and P (n = 12) and one control group K (n = 12). The basic research method was a twelve-week experiment. The experimental groups carried out resistance training - group T on the training simulator, group P in the form of arm stroke swimming. There was no training in group K. Control measurements included arm stroke swimming speed at a distance of 75 m during which the motor cycle length and the frequency of arm performance were determined. The measurements were carried out before and after the experiment. A positive transfer of the cumulative effect of upper limb resistance training on swimming speed at a distance of 75 m was found in groups T and P. The training transfer was higher in group T than in group P by 0.6%.